0.65x+0.05(18-X)=0.10(117)

Simple and best practice solution for 0.65x+0.05(18-X)=0.10(117) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.65x+0.05(18-X)=0.10(117) equation:


Simplifying
0.65x + 0.05(18 + -1X) = 0.10(117)
0.65x + (18 * 0.05 + -1X * 0.05) = 0.10(117)
0.65x + (0.9 + -0.05X) = 0.10(117)

Reorder the terms:
0.9 + -0.05X + 0.65x = 0.10(117)

Multiply 0.10 * 117
0.9 + -0.05X + 0.65x = 11.7

Solving
0.9 + -0.05X + 0.65x = 11.7

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-0.9' to each side of the equation.
0.9 + -0.05X + -0.9 + 0.65x = 11.7 + -0.9

Reorder the terms:
0.9 + -0.9 + -0.05X + 0.65x = 11.7 + -0.9

Combine like terms: 0.9 + -0.9 = 0.0
0.0 + -0.05X + 0.65x = 11.7 + -0.9
-0.05X + 0.65x = 11.7 + -0.9

Combine like terms: 11.7 + -0.9 = 10.8
-0.05X + 0.65x = 10.8

Add '-0.65x' to each side of the equation.
-0.05X + 0.65x + -0.65x = 10.8 + -0.65x

Combine like terms: 0.65x + -0.65x = 0.00
-0.05X + 0.00 = 10.8 + -0.65x
-0.05X = 10.8 + -0.65x

Divide each side by '-0.05'.
X = -216 + 13x

Simplifying
X = -216 + 13x

See similar equations:

| 2x+4y-6z=0 | | -(5x-7)-(2x-2)+7=-6(x-9)-(6x+4)+4 | | 1x+2+3=91.50 | | 3+38x=52x+2 | | (x-2)+(x-1)+x=117 | | 4(2x-3)+x=x-4 | | x-0.2=ln(1+x) | | 87.5=12.5(2x-2) | | 100=4x(4x+x) | | 5x-4(x-3)=8+2x | | (v^2+4v-5)(2v-4)=0 | | 100=4x(4x+1) | | 7(y+3)=5y+2 | | 2w-77=-4+77 | | 21k=72k | | 7n-3=4+12 | | (10t^2-4t+12)+(14t-3)= | | 24/30X35/30= | | 10-7a=80 | | 6/5*5/8 | | y=-2x^2-8x+6 | | 2b+5b=2 | | 7x+9=-x-15 | | 5x^2-18=-2+x^2 | | 6x+11y=1120 | | 19k=81+9k | | (-8a^4/b)^2 | | 8cosx-4=2 | | 2x+50=4x-20 | | 12=-2/9w | | 11.5d=23 | | 7x-14=3x+8 |

Equations solver categories